2019
DOI: 10.48550/arxiv.1906.04178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complexity phase diagram for interacting and long-range bosonic Hamiltonians

Abstract: Recent years have witnessed a growing interest in topics at the intersection of many-body physics and complexity theory. Many-body physics aims to understand and classify emergent behavior of systems with a large number of particles, while complexity theory aims to classify computational problems based on how the time required to solve the problem scales as the problem size becomes large. In this work, we use insights from complexity theory to classify phases in interacting manybody systems. Specifically, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Since these models do not typically conserve the number of bosons, our methods will need to be modified somewhat to remain applicable, although in certain limiting cases Lieb-Robinson bounds have nevertheless been obtained for such models [26]. We anticipate that our theorem will also have broad implications for the simulatability of the Bose-Hubbard model, which is conjectured to be a test of quantum supremacy in a future quantum computer [13,[43][44][45][46]. We hope to return to these interesting extensions of our work in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Since these models do not typically conserve the number of bosons, our methods will need to be modified somewhat to remain applicable, although in certain limiting cases Lieb-Robinson bounds have nevertheless been obtained for such models [26]. We anticipate that our theorem will also have broad implications for the simulatability of the Bose-Hubbard model, which is conjectured to be a test of quantum supremacy in a future quantum computer [13,[43][44][45][46]. We hope to return to these interesting extensions of our work in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion.-The above analysis of 2d circuits suggests that the finite-time teleportation transition may generally correspond to a transition in approximate sampling complexity [22,44]. Specifically, we consider the problem of sampling measurement outcomes from N qubits initialized in a product state and evolved under a finite-time unitary circuit.…”
Section: However S (N)mentioning
confidence: 99%
“…For example, the Lieb-Robinson light cone limits the correlation between sublattices [21]. Using this, it has been shown that up to time t ∼ (M/N ) 1/d , there exists an efficient classical algorithm to sample from the output distribution of general quadratic bosonic Hamiltonian dynamics [19,20]. In this work, we focus on a circuit model of random 2-local passive transformation and find a depth in which classical simulation of sampling is efficient.…”
Section: Problem Setupmentioning
confidence: 99%
“…On the other hand, when a quantum circuit is deep enough to implement a global Haarrandom unitary circuit that generates a large amount of entanglement, sampling from the probability distributions of the output state becomes classically intractable under plausible assumptions [9,10,17,18]. Indeed, under bosonic Hamiltonian dynamics, phase transition behavior of sampling arising from the evolution time has been diagnosed [19,20]. Whereas time-evolution dynamics under a bosonic Hamitonian using the Lieb-Robinson bound [21] has been studied in Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation